Axial compression behaviours of seawater and sea sand concrete-filled GFRP stub tubes at arctic low temperatures. (January 2022) - Xie, Jian; Wang, Zhe; Yan, Jia-Bao
Abstract: A series of low-temperature tests on axial compression behaviours of thirty stub columns were presented in this paper, which included eight hollow GFRP tubes (HFTs), six unconfined plain seawater and sea sand concrete columns (UPCCs), and sixteen seawater and sea sand concrete-filled GFRP tubes (CFFTs). Regarding the compression tests on CFFTs, axial compression load was applied to inside confined plain seawater and sea sand concrete column (CPCC) and GFRP tube concurrently. The studied parameters of this testing programme included loading schemes of monotonically or cyclically axial compression, low temperatures of 20, − 30, − 60, and − 80 °C, and diameter-to-thickness ratios of 20, 21, 30, 40, and 50. The failure modes, axially compressive load–strain curves, and compressive stress–strain curves of all columns at low temperatures have been revealed. Meanwhile, the influences of different parameters on ultimate compression strength and ultimate axial strain of CFFTs at low temperatures were detailly discussed. These results indicated that axial compression behaviours of CFFT stub columns have been improved at low temperatures. According to the test results, prediction formulae have been proposed to determine the ultimate compression resistance and ultimate axial strain of CFFTs reasonably but conservatively at low temperatures. Highlights: Low temperatures improve ultimate strength and elastic modulus of GFRP tube. Low-temperature envelope σ - ɛ curves of CFFTs behave closely to monotonic ones. Low temperatures greatly increase the ultimate compressive strength of CFFTs. Proposed equations predict well low-temperature compression behavior of CFFT.